Aksjologiczny wymiar rozstrzygnięć w teorii i praktyce resocjalizacji - Sztuka, Mariusz (Horyzonty Wychowania, 2017)
The author touches upon the issues of contemporary conditionsof rehabilitation activity from the perspective of changestaking place in the sphere of rehabilitation teleology, as well astransformations concerning phenomena of social pathology.Along with the progress observed in the area of the ability toexplain the basis and nature of deviation behaviours in a rationalway, the model of a deviant expressed mainly in moral or religiousterms is suffering from erosion. Simultaneously, a perceptibleincrease in the size of social pathology and thedisturbing changes in its nature in the perspective of the previousdecades, which is perceived as a fragment of a more generalcrisis of values, gives rise to the necessity of an urgent interventionof preventive and corrective kind. These circumstancesresult in a difficulty, which signals its presence on the level ofconcrete educational decisions, and also emphasizes certainconstant ambivalences constituting the professional role of rehabilitationpedagogue.